2019
DOI: 10.1097/nne.0000000000000730
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral Degree Preferences for Nurse Educators

Abstract: Background Current doctoral degree options may not meet needs of nurses desiring educator roles in academic or health care settings. Purpose The purpose of the study was to assess preferences for existing terminal degree options for nurse educators and determine the need for a new doctoral degree in nursing education. Method Nurses in practice, academia, and leadership nationwide (n = 826) answered a 19-item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In this instance, the collaboration allowed students to gain critical pedagogical training—often lacking in nursing doctoral education—and faculty to have assistance from a group of students who had received training in remote course development. 51 , 52 Elsewhere, many institutions have established mental health and wellbeing services for students and faculty, and encouraged both groups to be as flexible as possible while navigating changed learning structures. 53 While some faculty may be unaccustomed to allowing greater leeway in coursework and participation, absolutist approaches are not only unfeasible but potentially detrimental in the current circumstances.…”
Section: Tic Assumptions and Guiding Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, the collaboration allowed students to gain critical pedagogical training—often lacking in nursing doctoral education—and faculty to have assistance from a group of students who had received training in remote course development. 51 , 52 Elsewhere, many institutions have established mental health and wellbeing services for students and faculty, and encouraged both groups to be as flexible as possible while navigating changed learning structures. 53 While some faculty may be unaccustomed to allowing greater leeway in coursework and participation, absolutist approaches are not only unfeasible but potentially detrimental in the current circumstances.…”
Section: Tic Assumptions and Guiding Principlesmentioning
confidence: 99%
“…One example of a novel, successful collaboration is that of a university where PhD students were offered summer stipend funding to help faculty transition courses to online learning. In this instance, the collaboration allowed students to gain critical pedagogical training—often lacking in nursing doctoral education—and faculty to have assistance from a group of students who had received training in remote course development 51,52 . Elsewhere, many institutions have established mental health and wellbeing services for students and faculty, and encouraged both groups to be as flexible as possible while navigating changed learning structures 53 .…”
Section: Tic Assumptions and Guiding Principlesmentioning
confidence: 99%
“…In addition, a study of content in nursing PhD programs found that 64% of respondents (n = 826) indicated that content on teaching and learning, curriculum design, and course development waslacking in these programs. 8 Importantly, a study of nursing students' expectations of faculty also found that "knowing and using the proper education methods, techniques and strategies while teaching" was among the top 3 conditions regarded as essential to student success. 9 Taken together, these findings demonstrate the importance of pedagogical preparation for prospective nursing faculty to the success of both students and the profession more broadly.…”
Section: Problemmentioning
confidence: 99%
“…AACN is clear that neither the DNP nor the PhD explicitly provides educational preparation for graduates as nurse faculty. Similarly, King et al (2020) reported that 60% of respondents to their survey of 826 nurses expressed concern about the lack of curriculum and teaching-learning content in existing doctoral programs, suggesting a possible new practice doctoral degree, a doctor of nursing education. Addressing the lack of preparation of faculty for a career as nurse faculty by creating another new academic degree in nursing seems likely to cloud the already murky waters of academic degree options in nursing.…”
Section: Faculty Expertise and Areas Of Responsibilitymentioning
confidence: 99%
“…This clearly requires a more thorough analysis than is possible here. It also has been suggested that optional content be added in both DNP and PhD programs for those considering careers as academic nurse faculty (King et al, 2020). While laudable, it still would not assure those faculties have the requisite expertise as nurse educators, especially since many, particularly those pursuing advanced practice options in the discipline, might not decide until later to transition into a faculty role.…”
Section: Faculty Expertise and Areas Of Responsibilitymentioning
confidence: 99%